A novel HLA allele, HLA‐A*02:393, identified in a two generation Italian family. Issue 3 (19th August 2013) - Longa, L. A.; Perotti, L.; Piovano, F.; Prucca, M.; Menardi, G.; Peano, G.
Abstract : HLA‐A*02:393 differs by a single nucleotide substitution from both A*02:26 (A524G) and from A*02:40:01 (T527A)